Empowering Voices from Pesantren: The Emergence of Female Spiritual Leadership in Indonesia - Nugroho, Aris Dwi (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2024)
This research analyses women's spiritual leadership in building commitment in Islamic boarding schools. This is based on the basic assumption that women are considered unfit to be leaders because of gender aspects. This research uses a qualitative phenomenological approach. The data collection technique uses in-depth interviews, observation and documentation. Data analysis is carried out during data collection and after completing data collection within a certain period using data reduction techniques, data presentation, data verification and concluding. The research results show that the spiritual leadership of women displayed in Islamic boarding schools includes vision (short and long-term views), altruistic love (harmonious organizational culture), hope/faith (the expectations that underlie the vision and mission), calling (the soul's call for change), and membership (the need to be respected and understood). This research provides implications regarding the importance of supporting spiritual leadership in Islamic boarding schools through the development of vision, a harmonious culture, firm hope, a call for change, and a sense of belonging to strengthen women's role as influential spiritual leaders.